Kajian Teknis Pengolahan SHP menggunakan Shaking Table untuk Mengoptimalkan Kadar dan Recovery Sn di TB Batu Besi PT Timah Tbk - Kristina Damayanti Panjaitan; Janiar Pitulima; Delita Ega Andini (MINERAL, 2023)
PT Timah Tbk carried out the development by establishing TB Primer Batu Besi, East Belitung. The purpose of this study was to find out the variable setting of the shaking table in order to obtain optimal levels and recovery of Sn. The research method used is gravity concentration using a shaking table tool. The feed used is Remaining Processing Results from the primary shaking table. The experiment was carried out twice, the first experiment was carried out 27 times with a sample weight of ± 78 kg. Each experiment used 9 variations, namely the tilt of the shaking table (8°;8.5°;9°) and the stroke length (12mm, 14mm, 16mm). The second experiment used ±5 tons of material with the most optimal tool settings from the first experiment. The feed sample material and product shaking table were tested using the XRF and GCA tests. The analysis of the XRF test showed that the Sn content in the feed was 0.45%. GCA analysis shows that the associated minerals are cassiterite, ilmenite, monazite, pyrite, quartz, tourmaline, hematite and magnetite. The optimal setting for the operating variable of the shaking table is with a variation of the tilt of the shaking table 8° and a stroke length of 12 mm to obtain a concentrated Sn content of 8.04% and a concentrated Sn recovery of 20.75%. The second experiment obtained a total Sn recovery of 17.25%. If one additional SHP processing line is added to TB Batu Besi, the company's recovery will increase from ±15% to ±29.55%.